Analisis pengaruh tingkat pendidikan dan pertumbuhan ekonomi terhadap tingkat kemiskinan di Provinsi Jambi - Nurhasanah Nurhasanah; Muhammad Safri; Jaya Kusuma Edi (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2019)
The purpose of this research: (1) To know the development of education level and economic growth to the level of poverty in Jambi Province; (2) To know the influence of education level and economic growth to Poverty Level in Jambi Province. The method of analysis used in this study deskrptif analysis and quantitative analysis with the analysis tool is multiple linear regression. Data processing is done by using Microsoft Excel Software program and Eviews 8.0. The results of this study are the first overall development level of education (TP) during the period 2000-2016 on average increased by 0.64 percent. Economic growth in 2016 of 7.5 percent increase compared to the year 2015 of 5.9 percent. The four variables together significantly affect the poverty rate with the coefficient of TP of -0.080240, PE coefficient of -0.256608 percent. For the value of coefficient of determination (R2) of 0.614738 shows that TP and PE together affect the poverty rate of 61.47 while the rest of 38.53 percent explained by other variables not included in the model estimation. Keywords: Poverty Level, Education Level, and Economic Growth.